2023
DOI: 10.1177/00472441221141957
|View full text |Cite
|
Sign up to set email alerts
|

Cultural responses to the COVID-19 crisis in Greece: The first wave (March–May 2020)

Abstract: This article examines cultural responses to the COVID-19 pandemic in Greece during the first wave in spring 2020 approaching such responses not only as resulting from the fear of the virus but also as outcomes of larger historical processes. Analysing media material, surveys and discourses by politicians and health specialists the article argues that although Greece had a limited number of cases, most Greeks embraced the lockdown seeing COVID-19 as a threat. The government’s communication strategy highlighted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The present study showed a gap in students’ communication with their tutors because of the sudden and exclusive use of distance learning during the COVID-19 pandemic. Similarly, recent studies have identified the same gap, highlighting deep concerns about the level of interaction concerning face-to-face learning [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 75%
“…The present study showed a gap in students’ communication with their tutors because of the sudden and exclusive use of distance learning during the COVID-19 pandemic. Similarly, recent studies have identified the same gap, highlighting deep concerns about the level of interaction concerning face-to-face learning [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 75%